2019
DOI: 10.21608/adjg.2019.42313
|View full text |Cite
|
Sign up to set email alerts
|

The Remineralizing Effect of Incorporating Ca-Phosphate and Ca-Fluoride Nanoparticles into the Self-Etch Adhesives Used in Restoring Class I Cavities

Abstract: Purpose: This study was carried out to investigate the remineralizing effect of amorphous calcium phosphate (ACP) and calcium fluoride (CaF 2) nanoparticles incorporated in two-step self etch-adhesives (in vivo). Materials and Methods: The nanoparticles were incorporated into the bond of Clearfil TM SE Bond at a mass fraction of 10%. A total of ten patients in the age range of 17-30 years old, having at least 3 carious lower molars, were enrolled in this study (split mouth design). Class I cavity preparation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…5,11,12 A previous study used CaF 2 nanoparticle fillers in the adhesive and reported remineralization of caries-affected dentin. 13 In another study, Mitwalli et al also witnessed and demonstrated that CaF 2 containing nanocomposites revealed resilient antibacterial and ion releasing properties without any significant effect exerted on the material's mechanical properties. 14 Thus, it can be anticipated that CaF 2 as a filler would improve dentin adhesives' properties.…”
Section: Introductionmentioning
confidence: 98%
“…5,11,12 A previous study used CaF 2 nanoparticle fillers in the adhesive and reported remineralization of caries-affected dentin. 13 In another study, Mitwalli et al also witnessed and demonstrated that CaF 2 containing nanocomposites revealed resilient antibacterial and ion releasing properties without any significant effect exerted on the material's mechanical properties. 14 Thus, it can be anticipated that CaF 2 as a filler would improve dentin adhesives' properties.…”
Section: Introductionmentioning
confidence: 98%
“…In the current study, single visit caries excavation leaving only caries affected dentin at the cavity floor was performed as this approach has a lower risk for pulp exposure than two-visit selective caries excavation and enables the affected dentin at the cavity floor to be mineralized (10,21) . Caries detector dye was used as it has been shown to be useful in the detection and removal of caries affected dentin (22) .…”
Section: Discussionmentioning
confidence: 99%
“…CaF 2 nanoparticles reinforce many properties of DAs, but they are largely based on their remineralization capabilities and antibacterial potential. Essam et al previously incorporated CaF 2 nanoparticles in two-step self-etch adhesives in an in vivo study and reported that due to the presence of these filler particles, remineralization of the caries-affected dentin was noticed [ 65 ]. The incorporation of CaF 2 nanoparticles possessing high surface area in dental composites results in overall high levels of fluoride and calcium ions, even at low filler concentration [ 66 ].…”
Section: Bioactive Inorganic Fillersmentioning
confidence: 99%